Use of geographic information systems for aquaculture and recommendations for development of spatial tools - Lynne Falconer; Anne Lise Middelboe; Hanne Kaas; Lindsay G. Ross; Trevor C. Telfer (Reviews in Aquaculture, 2020)
There are many spatial issues associated with aquaculture which must be understood in order to support sustainable development and mitigate other potential issues. Geographic Information Systems (GIS) are used for investigation, analysis and modelling of aquaculture and there have been a considerable number of studies since the late 1980s. However, despite the range of applications, GIS is still often underutilized and stakeholders have requested more GIS‐based tools to support management and regulation of the sector. Consequently, there is a need to establish a knowledge base of existing applications and identify the challenges and opportunities to encourage development of tools that address user needs. This study presents a quantitative analysis of primary scientific literature, focusing on over 200 studies, to enable a comprehensive overview of the application of GIS and the trends associated with its use for aquaculture. Furthermore, there is a detailed assessment of the considerations when developing GIS‐based tools for aquaculture which culminates in five key recommendations regarding (i) usability of the tool; (ii) data requirements; (iii) accessibility to end user; (iv) capabilities and training requirements; and (v) longevity of the tool. These recommendations can guide future development and application of tools to support aquaculture planning and management and assess spatial issues relevant for the sector.